STRATEGI GURU MENGATASI KESULITAN SISWA MEMBACA AL-QURAN DI MTS S AL-MUNAWAROH KEPAHIANG - Paiza wati; Ihsan nul hakim; Muhammad idris (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to of this research is to determine the strategy of Al-Qur'an teachers in overcoming students' difficulties in reading the Al-Qur'an at MTs S 02 Al-Munawwaroh and to determine the factors causing students' difficulties in reading the Al-Qur'an at MTs S 02 Al-Munawwaroh. The results of this research indicate that research students at MTs S 02 Al-Munawwaroh experience difficulties in reading the Al-Qur'an because the first factor is their lack of interest in reading the Al-Qur'an, secondly because their background does not provide such motivation. parents who do not really advise their children to study the Koran, thirdly because there is no awareness that the Koran is a need, for them that need is work. The influencing factors are the awareness factor and lack of motivation on the part of the students so that it is very difficult for students to learn the Al-Qur'an, and because technology is becoming increasingly sophisticated students are more interested in this technology than learning to read the Al-Qur'an. The activity of learning to read the Koran has not been carried out well. This can be seen from the behavior of students who are not enthusiastic and are lazy when reading the Al-Qur'an even though some students are interested and want to learn to read the Al-Qur'an.